Evidence-based recovery strategies in futsal : a narrative review - Nemčić, Tihana (Array, 2021)
Futsal (FT) can be defined as a multiple sprint sport with intermittent high-intensity activities. It could be considered one of the most demanding team sports due to the FT player"s heart rate mean of approximately 90%, work to rest ratio of 1:1 and activity changes every three seconds. Besides, unlimited number of substitutions, size of the pitch, a smaller ball and constant proximity of the opponent that puts extremely high demands on FT players are the main characteristics of the game. With studies reporting that participating in a FT match provokes muscle damages and inflammations, with a high injury incidence, it is of vital necessity to examine the most efficient methods providing fast recovery of FT players between practice sessions and matches played. Research studies focused on recovery methods in other team sports such as basketball, volleyball, and rugby, among others, reported benefits of passive recovery (massage, water therapy, stretching), active recovery and nutritional techniques. However, for the best of the authors" knowledge, a limited number of recovery methods has been provided for the game of FT. The most effective recovery methods for FT players are only found to be photobiomodulation therapy and optimal sleeping regimen. Thereby, the main aim of the current narrative review is to present available scientific literature of recovery methods that may have positive effects on FT players.